Pollution of a sea water collection by chlorinated pestcides (DDT). - ΠΑΝΕΤΣΟΣ, Α.; ΚΙΛΙΚΙΔΗΣ, Σ.; ΨΩΜΑΣ, Ι. (Journal of the Hellenic Veterinary Medical Society, 2019)
A case of pollution of a salt lake by chlorinated pesticides (DDT) is described. Besides the change in the water composition, the authors noted a decrease by 50 % of the NaCI, Ca** and Mg** content of this water in comparison with that of the neighbouring sea. The amounts of total DDT residues were: 414 ng/l.of water, 0.040 ppm in the surrounding soil, 176.655 ppm in fishes fat and 62.533 ppm in shellfishes fat. The pollution resulted in the massive death of the fauna of the lake. The origin of the pollution and its influence on the sea fauna are discussed